Psychological Treatment Effects Unrelated to Hair-Cortisol and Hair-BDNF Levels in Chronic Tinnitus - Basso, Laura; Boecking, Benjamin; Neff, Patrick; Brueggemann, Petra; Mazurek, Birgit; Peters, Eva M. J. (Frontiers in Psychiatry, 2022)
Background: Currently, there are no objective markers to measure treatment efficacy in chronic (distressing) tinnitus. This study explores whether stress-related biomarkers cortisol and brain-derived neurotrophic factor (BDNF) levels measured in hair samples of chronic tinnitus patients change after compact multimodal tinnitus-specific cognitive behavioral therapy. Methods: In this longitudinal study, hair-cortisol and hair-BDNF levels, self-reported tinnitus-related distress (Tinnitus Questionnaire; TQ), and perceived stress (Perceived Stress Questionnaire; PSQ-20) were assessed before and 3 months after 5 days of treatment in N=80 chronic tinnitus patients. Linear mixed-effects models with backward elimination were used to assess treatment-induced changes, and a cross-lagged panel model (structural equation model) was used for additional exploratory analysis of the temporal associations between TQ and hair-BDNF. Results: At follow-up, a reduction in TQ (p<0.001) and PSQ-20 scores (p=0.045) was observed, which was not influenced by baseline hair-cortisol or hair-BDNF levels. No changes in biomarker levels were observed after treatment. Exploratory analysis tentatively suggests that the influence of baseline TQ scores on hair-BDNF at follow-up (trend; p=0.070) was stronger than the opposite effect of baseline hair-BDNF on TQ scores at follow-up (n.s.). Discussion: While the treatment effectively reduced tinnitus-related distress and perceived stress in chronic tinnitus patients, this effect was not mirrored in biological changes. However, the lack of changes in hair-cortisol and hair-BDNF levels might have been influenced by the treatment duration, follow-up interval, or confounding medical factors, and therefore must be interpreted with caution. The relationship between tinnitus-related distress and hair-BDNF levels should be explored further to obtain a better understanding of stress-related effects in chronic tinnitus.